Ethnic pluralism and ethnic relations in Sarawak - Jehom, Welyne Jeffrey (Universiti Kebangsaan Malaysia, 2002)
This paper discusses the historical and contemporary dynamics of ethnic pluralism and ethnic relations in Sarawak. The discussion is based on numerous in-depth interviews that were conducted throughout 1999-2001. Results showed that the dynamics of ethnic pluralism and ethnic relations in contemporary Sarawak are basically molded by the history of the earlier patterns of interaction and relations. Additionally, pluralist tolerances in many respects contribute towards forging a stronger foundation for closer interactions. The study also found intermarriages of people with different cultural and religious backgrounds, tolerance of religions and religious places, the participation and cooperation of the native, Malay and Chinese in business activities and tolerance in cultural and religious festivities to be the most prominent features of ethnic pluralism in present-day Sarawak.